Does periodontitis affect mean platelet volume(MPV) and plateletcrit (PCT) levels in healthy adults? - Ustaoglu,Gülbahar (2020)
SUMMARY OBJECTIVE Periodontitis may stimulate infectious and immune response and cause the development of atherogenesis, coronary heart disease, and myocardial infarction. The aim of this study was to compare the plateletcrit (PCT) and mean platelet volume (MPV) levels derived from complete blood count (CBC) tests in patients suffering from stage 3 periodontitis with those of healthy individuals without periodontal disease. METHODS The study included 57 patients (28 females and 29 males) with Stage 3 Periodontitis and 57 volunteering individuals (31 females and 26 males) who were periodontally healthy. The age of study participants ranged from 18 to 50 years. Their periodontal condition was investigated with probing depth (PD), clinical attachment level, bleeding on probing, and plaque index. Leukocyte (WBC) and erythrocyte count (RBC), hemoglobin (Hb) and hematocrit (HCT) levels, mean corpuscular volume (MCV) and red cell distribution width (RDW), thrombocyte count, mean platelet volume (MPV), plateletcrit (PCT ), and neutrophil and lymphocyte counts were evaluated based on the CBC test results of the study participants. RESULTS PCT, WBC, Neutrophil, and MPV values were found to be significantly higher in the periodontitis group (p<0.05). There were no significant differences in RBC counts, Hb, HCT, MCV, RDW, and platelet and lymphocyte counts between the two study groups (p>0.05). CONCLUSIONS PCT and MPV levels may be a more useful marker to determine an increased thrombotic state and inflammatory response in periodontal diseases.